The Representation of Female Roles in the Recommended Indonesian English Language Teaching (ELT) Textbook for 10th Grade Students: A Critical Discourse Analysis - Luthfiah, Desty Rahmasari; Yanto, Elih Sutisna; Kamil, Acep Bahrum (Jurnal Ilmiah Wahana Pendidikan, 2024)
In spite of numerous investigations conducted on the portrayal of gender in language textbook, in Indonesia gender representation exploration using ELT textbook for senior high school is still relatively under-researched especially in social context such as domestic chore, careers, academic achievement and participation, hobbies and interests. To fill this gap, this research is designed to examine the representation of females in the mandated ELT textbook for senior high school especially for 10th grade students using critical discourse analysis (CDA) as a research approach. The aim of this study is to reveal the representation of female roles in the English foreign language (EFL) textbook reflects and reinforces gender stereotypes and expectations in society. By using Theo Van Leeuwen’s (2008) theory, it was found that gender representations are still found in this ELT textbook. The representation of female roles in it are still portrayed in traditional forms. This research provides recommendations for textbook publishers, authors, and teachers to pay more attention to gender equality in the design and use of ELT textbooks